Optimization switching angle based on practical swarm optimization (PSO) of A DSP-TMS320F2812 controlled for multilevel inverter - Rasheed, Mohammed; Omar, Rosli; ., Nizam; Sulaiman, Marizan (International Journal of Engineering and Technology, 2018)
In this paper optimization switching angle based on practical swarm optimization (PSO) of a Digital Signal Processing DSP-TMS320F2812 controlled for cascaded H-bridge multilevel inverter (CHB-MLI). The selective harmonics elimination (SHE) method was analysed based on Newton Raphson (NR) and PSO techniques for solution non-linear equation's derived for computing optimal switching angles of a modified (CHB-MLI) for harmonic minimization. The proposed techniques have been comparison between NR and PSO techniques related to optimization in order minimize harmonic distortion of output voltage. The main aims of this paper, testing of a laboratory the modified topology of the CHB-MLI for a three phase prototypes for five levels. The Digital Signal Processing (DSP) TMS320F2812 is used to implement these modified inverters control schemes using NR and PSO method. The proposed controller was then coded into a DSP TMS320F2812 board. The inverter offers much less THD using PSO scheme compared with the NR scheme. The performance of the proposed controllers based on NR and PSO techniques are implemented in a prototype, of results are compared.Â Â